Mature Cystic Teratoma Complicated with Pseudo - Meigs Syndrome and Elevated CA-125 Level in Puerperium: A Case Presentation and Review of the Literature - Karataylı, Rengin; Gezginç, Kazım; Kantarcı, Ali Haydar; Acar, Ali (Gynecology Obstetrics & Reproductive Medicine, 2012)
This report presents a mature cystic teratoma complicated in puerperium with acute abdominal pain, diffuse ascites, hydrotorax and adnexial mass. A 42 years old multiparous patient, admitted to our clinic with abdominal distension, dyspnea, and diffuse abdominal pain. It was learnt that patient had normal spontaneous vaginal live birth 10 days earlier. There was a 6 cm sized cystic lesion with solid components originating from left adnexial area on pelvic ultrasonography. Besides, there was diffuse ascites. Abdominal CT revealed high probability for dermoid cyst or ovarian malignancy. CA-125 levels were increased. During laparotomy, 3000cc of ascites was drained and left salphingoopherectomy was performed. Frozen section result was benign. Exact pathology result was reported as mature cystic teratoma. In puerperal period, benign ovarial pathologies should be kept in mind in patients presenting with diffuse ascites and ovarial mass.